New Triterpenoids and Anti-Inflammatory Constituents from Glinus oppositifolius - Chen, Jih-Jung; Yang, Chang-Syun; Chen, Yu-Hui; Chao, Che-Yi; Chen, Yu-Chang; Kuo, Yeuh-Hsiung (Molecules, 2023)
Three new triterpenoids—spergulagenin B (1), spergulagenin C (2), and spergulagenin D (3)—were isolated from the aerial part of Glinus oppositifolius, along with 17 known compounds (4–20). The structures of these new compounds were identified by spectroscopic and MS analyses. Compounds 3, 5, 19, and 20 were evaluated for inhibition of nitric oxide production in LPS-stimulated RAW 264.7 cells with IC50 values of 17.03, 18.21, 16.30, and 12.64 μM, respectively. Compounds 3, 5, and 20 exhibited inhibitory effects on LPS-induced nitric oxide production in RAW 264.7 cells with IC50 values of 18.35 ± 1.34, 17.56 ± 1.41, and 14.27 ± 1.29 μM, respectively.